Impact of Temperature on the Strength Development of the Tailing-Waste Rock Backfill of a Gold Mine - Bin Han; Shengyou Zhang; Wei Sun (Advances in Civil Engineering)
This study investigated the influencing rules of curing temperature (5, 10, 16, and 20°C), cement ratio (8%, 10%, 12%, and 14%), and mass concentration (70%, 73%, 74%, and 75%) on the strength of backfill. In addition, a scanning electron microscope (SEM) is employed to analyze the microtopography of the backfill. Experimental results indicate that the uniaxial compressive strength (UCS) of the backfill decreases as the curing temperature diminishes; temperature substantially influences the earlier strength of backfill (it is much significant below 10°C). In addition, as the cement ratio rises, the critical point for the impact of temperature on strength gradually moves toward a low-temperature zone; in pace with the slurry mass concentration increase, the compressive strength of the backfill also rises and its rate of increase enlarges after going beyond the critical concentration. In case the curing temperature is lower than 10°C, the extent of hydration is also low inside the backfill. Through experiments, the critical concentration of slurry in the Jinying gold mine is determined as 73%, and the critical interval of the cement ratio ranged between 10% and 12%. Corresponding measures can be taken to increase the strength of backfill in the Jinying Gold Mine by 129.9%. As a result, backfill collapse is effectively controlled.